Gaya Kepemimpinan dalam Perspektif Generasi Millenial - Mustomi, Dede; Reptiningsih, Eni (2020)
This study aims to see how a generation sees leadership style. The focus of this study is to assess leadership styles in millennial generation perspectives. This research is a descriptive research. Data collection was used by survey method by distributing questionnaires to respondents. In this study the intended respondent is the millennial generation, that is, the generation born in the 80s, the generation born in the 90s and the generation born in the 2000s. All generations received the same quota, each with 50 respondents. Respondents were asked to choose one of eight leadership styles. There are eight leadership styles that respondents will choose according to the criteria they want the most. Dictatorial leadership style, militaristic leadership style, paternalistic leadership style, participative leadership style, laissez faire leadership style, leadership style free of control, charismatic leadership style and finally democratic leadership style. They are asked to choose a leader who has a leadership style that best suits their criteria.